Intensity-dependent degenerate and non-degenerate nonlinear optical absorption of direct-gap semiconductors - Hannes, Wolf-Rüdiger; Krauß-Kodytek, Laura; Ruppert, Claudia; Betz, Markus; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXIII)

Higher-order contributions and nonperturbative effects in the nondegenerate nonlinear optical absorption of semiconductors using a two-band model - Hannes, Wolf-Rüdiger; Meier, Torsten (Physical Review B)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Attosecond temporal confinement of interband excitation by intraband motion - Song, Xiaohong; Zuo, Ruixin; Yang, Shidong; Li, Pengcheng; Meier, Torsten; Yang, Weifeng (Optics Express)

Bloch oscillations of multidimensional dark soliton wave packets and light bullets - Driben, R; Ma, Xuekai; Schumacher, Stefan; Meier, Torsten (Optics Letters)

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Efficient frequency conversion by combined photonic–plasmonic mode coupling - Weber, N.; Hoffmann, S. P.; Albert, M.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Stacked Self-Assembled Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Rieger, Torsten; Meertens, Doris; Pawlis, Alexander; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
We have investigated the stacking of self-assembled cubic GaN quantum dots (QDs) grown in Stranski–Krastanov (SK) growth mode. The number of stacked layers is varied to compare their optical properties. The growth is in situ controlled by reflection high energy electron diffraction to prove the SK QD growth. Atomic force and transmission electron microscopy show the existence of wetting layer and QDs with a diameter of about 10 nm and a height of about 2 nm. The QDs have a truncated pyramidal form and are vertically aligned in growth direction. Photoluminescence measurements show an increase of the intensity with increasing number of stacked QD layers. Furthermore, a systematic blue-shift of 120 meV is observed with increasing number of stacked QD layers. This blueshift derives from a decrease in the QD height, because the QD height has also been the main confining dimension in our QDs.
Keywords: cubic crystals; GaN; molecular beam epitaxy; quantum dots

Signatures of transient Wannier-Stark localization in bulk gallium arsenide - Schmidt, C.; Bühler, J.; Heinrich, A.-C.; Allerbeck, J.; Podzimski, R.; Berghoff, D.; Meier, Torsten; Schmidt, Wolf Gero; Reichl, C.; Wegscheider, W.; Brida, D.; Leitenstorfer, A. (Nature Communications)

Signatures of transient Wannier-Stark localization in bulk gallium arsenide - Schmidt, Claudia; Bühler, J.; Heinrich, A.-C.; Allerbeck, J.; Podzimski, R.; Berghoff, Daniel; Meier, Torsten; Schmidt, Wolf Gero; Reichl, C.; Wegscheider, W.; Brida, D.; Leitenstorfer, A. (Nature Communications)

Coherent optical spectroscopy of charged exciton complexes in semiconductor nanostructures - Akimov, Ilya; Poltavtsev, Sergey V.; Salewski, Matthias; Yugova, Irina A.; Karczewski, Grzegorz; Wojtowicz, Tomasz; Maciej, Wiater; Reichelt, Matthias; Meier, Torsten; Yakovlev, Dmitri; Bayer, Manfred (Ultrafast Phenomena and Nanophotonics XXII)

Coherent optical spectroscopy of charged exciton complexes in semiconductor nanostructures - Akimov, Ilya; Poltavtsev, Sergey V.; Salewski, Matthias; Yugova, Irina A.; Karczewski, Grzegorz; Wojtowicz, Tomasz; Maciej , Wiater; Reichelt, Matthias; Meier, Torsten; Yakovlev, Dmitri; Bayer, Manfred (Ultrafast Phenomena and Nanophotonics XXII)

Vortex Multistability and Bessel Vortices in Polariton Condensates. - Ma, Xuekai; Schumacher, Stefan (Physical Review Letters)

Microscopic theory of cavity-enhanced single-photon emission from optical two-photon Raman processes - Breddermann, Dominik; Praschan, Tom; Heinze, Dirk Florian; Binder, Rolf; Schumacher, Stefan (Physical Review B)

Spin and Geometric Phase Control Four-Wave Mixing from Metasurfaces - Li, Guixin; Sartorello, Giovanni; Chen, Shumei; Nicholls, Luke H.; Li, King Fai; Zentgraf, Thomas; Zhang, Shuang; Zayats, Anatoly V. (Laser & Photonics Reviews)

Controlling the phase of optical nonlinearity with plasmonic metasurfaces - Chen, Shumei; Li, Guixin; Cheah, Kok Wai; Zentgraf, Thomas; Zhang, Shuang (Nanophotonics)

Imaging through Nonlinear Metalens Using Second Harmonic Generation - Schlickriede, Christian; Waterman, Naomi; Reineke, Bernhard; Georgi, Philip; Li, Guixin; Zhang, Shuang; Zentgraf, Thomas (Advanced Materials)

Spiral modes supported by circular dielectric tubes and tube segments - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optical and Quantum Electronics)
The modal properties of curved dielectric slab waveguides are investigated. We consider quasi-confined, attenuated modes that propagate at oblique angles with respect to the axis through the center of curvature. Our analytical model describes the transition from scalar 2-D TE/TM bend modes to lossless spiral waves at near-axis propagation angles, with a continuum of vectorial attenuated spiral modes in between. Modal solutions are characterized in terms of directional wavenumbers and attenuation constants. Examples for vectorial mode profiles illustrate the effects of oblique wave propagation along the curved slab segments. For the regime of lossless spiral waves, the relation with the guided modes of corresponding dielectric tubes is demonstrated.
Keywords: tet_topic_waveguide

Simulation of Second Harmonic Generation from Photonic Nanostructures Using the Discontinuous Galerkin Time Domain Method - Grynko, Yevgen; Förstner, Jens (Recent Trends in Computational Photonics)
We apply the Discontinuous Galerkin Time Domain (DGTD) method for numerical simulations of the second harmonic generation from various metallic nanostructures. A Maxwell–Vlasov hydrodynamic model is used to describe the nonlinear effects in the motion of the excited free electrons in a metal. The results are compared with the corresponding experimental measurements for split-ring resonators and plasmonic gap antennas.
Keywords: tet_topic_numerics; tet_topic_shg; tet_topic_meta

Systematic study of the influence of coherent phonon wave packets on the lasing properties of a quantum dot ensemble - Wigger, Daniel; Czerniuk, Thomas; Reiter, Doris E; Bayer, Manfred; Kuhn, Tilmann (New Journal of Physics)
Coherent phonons can greatly vary light–matter interaction in semiconductor nanostructures placed inside an optical resonator on a picosecond time scale. For an ensemble of quantum dots (QDs) as active laser medium, phonons are able to induce a large enhancement or attenuation of the emission intensity, as has been recently demonstrated. The physics of this coupled phonon–exciton–light system consists of various effects, which in the experiment typically cannot be clearly separated, in particular, due to the complicated sample structure a rather complex strain pulse impinges on the QD ensemble. Here we present a comprehensive theoretical study how the laser emission is affected by phonon pulses of various shapes as well as by ensembles with different spectral distributions of the QDs. This gives insight into the fundamental interaction dynamics of the coupled phonon–exciton–light system, while it allows us to clearly discriminate between two prominent effects: the adiabatic shifting of the ensemble and the shaking effect. This paves the way to a tailored laser emission controlled by phonons.